2009
DOI: 10.1186/cc7736
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of haemorrhagic shock with normal saline vs. lactated Ringer's: effects on oxygenation, extravascular lung water and haemodynamics

Abstract: Introduction Pulmonary oedema and impairment of oxygenation are reported as common consequences of haemorrhagic shock and resuscitation (HSR). Surprisingly, there is little information in the literature examining differences in crystalloid type during the early phase of HSR regarding the development of pulmonary oedema, the impact on oxygenation and the haemodynamic response. These experiments were designed to determine if differences exist because of crystalloid fluid type in the development of oedema, the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 30 publications
4
30
0
1
Order By: Relevance
“…Resuscitation with lactated Ringer's solution (containing equal amounts of D and L isomers of lactate) have been associated with modulation of the inflammatory response, up-regulation of iNOS activity, and subsequent proinflammatory mediator synthesis compared with resuscitation using hypertonic saline and pentoxifylline solution [24,25]. Our results also show that iNOS expression of 2LR group in spleen were significantly higher than HS group at 6 h in wild type mice.…”
Section: Discussionsupporting
confidence: 59%
“…Resuscitation with lactated Ringer's solution (containing equal amounts of D and L isomers of lactate) have been associated with modulation of the inflammatory response, up-regulation of iNOS activity, and subsequent proinflammatory mediator synthesis compared with resuscitation using hypertonic saline and pentoxifylline solution [24,25]. Our results also show that iNOS expression of 2LR group in spleen were significantly higher than HS group at 6 h in wild type mice.…”
Section: Discussionsupporting
confidence: 59%
“…Similar findings in swine models have shown significantly more hyperchloremia, acidosis, and increased base deficit with NS use, compared with LR. 22,23,34 Our results also confirm the results of the only prospective RCT comparing crystalloid solutions in trauma patients, recently completed in 2014 by Young et al, 35 where NS was compared with Plasma-Lyte A solution (a calcium-free balanced salt solution). Their study found that base deficit became more positive, pH was higher, and Cl was lower in the group of patients randomized to receive Plasma-Lyte A when compared with the NS arm.…”
Section: Discussionsupporting
confidence: 93%
“…A midline laparotomy and splenectomy were also performed. Splenectomy was performed due to the spleen's ability to sequester variable amounts of blood and is commonly done in swine models of hemorrhagic shock [10]. A Foley catheter was placed in the urinary bladder via stab cystostomy and a catheter was secured in the inferior vena cava (IVC).…”
Section: Study Design and Instrumentationmentioning
confidence: 99%